(untitled) (Justicia &Derecho, 2023)
The following article refers to the case Víctor Pey Casado and Fundación Presidente Allende v. Republic of Chile, the longest in the ICSID system and is currently in the execution phase before the Spanish justice system. We will review the factual and procedural aspects regarding the current procedural situation and the particularity of the exorbitant amount for which the arbitration award against the State of Chile pretends to enforcement in a foreign jurisdiction.